2008
DOI: 10.1089/oli.2008.0145
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytokine Secretion Owing to Multiple CpG Side Chains of DNA Duplex

Abstract: Unmethylated CpG sequences (CpG ODN) stimulate Toll-like receptor 9 (TLR9) to activate innate immunity. We made DNA duplexes from poly(dT)320 and CpG ODN with (dA)40 attached at the 3' end. Circular dichroism and gel electrophoresis indicated that the CpG parts turned outward from the duplex. When we changed the CpG ODN/poly(dT) molar ratio, the amount of IL-12 secreted from J774A.1 cells (murine macrophage-like) reached the maximum at the compositions with two to four CpG portions in one duplex, while the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Adenoviruses activate the innate immunity through Toll-like receptor–dependent (TLR-dependent) as well as TLR-independent pathways, causing up-regulation of type I IFNs and inflammatory cytokines 42. TLR-9 has been identified as a pattern recognition receptor (PRR) for DNA containing unmethylated CpG motifs 43, 44. TLR-2 and TLR-9 have been implicated in the innate response to Ad 45.…”
Section: Overview Of Immune Responses In Adenoviral Vector Mediated Gmentioning
confidence: 99%
“…Adenoviruses activate the innate immunity through Toll-like receptor–dependent (TLR-dependent) as well as TLR-independent pathways, causing up-regulation of type I IFNs and inflammatory cytokines 42. TLR-9 has been identified as a pattern recognition receptor (PRR) for DNA containing unmethylated CpG motifs 43, 44. TLR-2 and TLR-9 have been implicated in the innate response to Ad 45.…”
Section: Overview Of Immune Responses In Adenoviral Vector Mediated Gmentioning
confidence: 99%
“…Another study previously demonstrated that increasing the molar ratio of CpG on a DNA duplex induced increasing secretion of IL-12 44 . To investigate if the number of CpGs influences the immune polarization, we kept constant the CpG 3.5 nm spacing, antigens per DNA origami particle, and number of particles, but only increased the number of CpGs per particle from 12 to 63 (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Overall, DoriVac improved both CD4 and CD8 T cell proliferation, activation, and cytokine secretion, most noticeably with a CpG spacing of 3.5 nm and 18 CpGs per SQB. Previous studies also investigated other CpG engineering strategies, such as 3’-3’ linked CpG immunomer 43 , CpG side chains of DNA duplex 44 , DNA dendrimer with looped CpG 52 , and G-quadruplex-based CpG 53,54 All these studies indicated that higher-order CpG display may needed for enhanced immune activation. We were able to engineer narrower nano-spacing of CpG than in previous DNA-origami studies due to the compact structure of SQB.…”
Section: Discussionmentioning
confidence: 99%
“…The allostericity is probably related to the fact that dimerization of TLR9 is necessary for its activation (5). In addition, our recent study has shown that the flexibility of the polymer containing CpG DNA is a key to induce the large amount of IL-12 (29). Once one CpG branch binds to one TLR9 dimer, the polymer is locked adjacently to the vesicle surface where other TLR9 dimers are present.…”
Section: Resultsmentioning
confidence: 99%